High temperature stress and its influence on surface rumpling in NiCoCrAlY bond coat. (15th October 2017) - Yang, Lixia; Zou, Zhonghua; Kou, Zongde; Chen, Ying; Zhao, Guangming; Zhao, Xiaofeng; Guo, Fangwei; Xiao, Ping
Abstract: The objective of this work is to develop a methodology to measure the high temperature stress in the bond coat, and investigate its role on the surface rumpling. We first presented an analytical model to evaluate the high temperature stress using X-ray sin 2 Ψ technique coupling with the curvature measurement at room temperature. A typical NiCoCrAlY bond coat with a Hastelloy-X substrate was employed as a model sample. During exposure at 1150 °C, the bond coat was under tension at high temperature, increasing parabolically from 1.05 MPa after 12 h to 3.81 MPa after 120 h. To understand its effect on the surface rumpling, the bond coat surface roughness was recorded as a function of time, and compared with a bulk NiCoCrAlY alloy. A strong correlation between the bond coat stress and the surface roughness was identified. In addition, the origination of the bond coat stress and the rumpling mechanism were discussed. It was revealed that the high temperature stress in the bond coat was caused by the volume shrinkage from β-γ transformation, mainly due to the inter-diffusion. The grain sliding accompanied with diffusional creep in response to the bond coat stress controls the roughening. Graphical abstract: Image